Procrastination and academic motivation among students before and during the Covid-19 pandemic - Tisocco, Franco (2025)
The study assessed undergraduates’ procrastination and self-determined academic motivation during the Covid-19 pandemic compared with prepandemic times. Participants were 1,486 students attending public universities from Buenos-Aires-City-and-environs in Argentina (Mage = 26.74, SD = 7.88; 85% female, 15% male). A subtotal of 905 (61%) students participated pre-pandemic (January 2020) during face-to-face learning, and 581 (39%) participated during the pandemic (July 2021) during online learning. At both times, participants provided sociodemographic information and completed the Tuckman Procrastination Scale and the Academic Motivation Scale. Hierarchical multiple regression analyses were conducted to assess the relations between procrastination and academic motivation in students before compared to during the pandemic. A small but significant increase in procrastination was observed when comparing the pre- and duringpandemic groups: the risk of being classified as a procrastinator during the pandemic was estimated to be 22% higher (CI95 = 9%, 35%) compared with pre-pandemic times. Academic motivation was observed to remain stable, indicating evidence of minimal pre-during pandemic differences. Results suggest that, during the pandemic, procrastination in students rose, but academic motivation remained stable. These findings provide novel insights into psychological variables that affect student learning. In this vein, educators should be aware that students could procrastinate more within online learning contexts during a pandemic; thus, further research is needed to understand how to support students in this context.